2021
DOI: 10.3390/educsci11060288
|View full text |Cite
|
Sign up to set email alerts
|

Student and Tutor Satisfaction with Problem-Based Learning in Azerbaijan

Abstract: This article examines tutors’ and students’ satisfaction with the implementation of problem-based learning (PBL) at the Azerbaijan University of Architecture and Construction. A total of 28 pilot academic staff members and their students participated in PBL during one semester and received a questionnaire about their experiences at the end of the semester. In total, 649 students were involved in the intervention. Descriptive statistics and factor analyses were used to analyze the data. In total, the response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Nandi [10] concluded that combining PBL with the conventional teaching can train undergraduate medical students effectively. Our students in this study also considered PBL as a teaching modality that led to satisfactory learning as supported by a study in Azerbaijan where the students and faculty regarded it as an effective learning strategy [11].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Nandi [10] concluded that combining PBL with the conventional teaching can train undergraduate medical students effectively. Our students in this study also considered PBL as a teaching modality that led to satisfactory learning as supported by a study in Azerbaijan where the students and faculty regarded it as an effective learning strategy [11].…”
Section: Discussionmentioning
confidence: 57%
“…Here in this study, a strongly positive correlation between the PBL problem (case scenario) and PBL session can be taken as evidence that a well-written scenario can lead to successful conduction of the session. In addition, we can reiterate that a well-written case or problem has a positive impact on students learning a well written tutor guide could help the nonsubject expert tutor understand the case to facilitate the students effectively [11]. A well-written case can be considered as a strong foundation for the whole curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Portuguez and Zermeno (2020) has shown that online learning focused on real-world problems can pique learners' interest and promote more meaningful learning. Despite being implemented through online channels, the benefits of the PBL approach remain relevant, as students are able to apply the knowledge gained to critical thinking (Sattarova, Groot, & Arsenijevic, 2021). Therefore, the online presentation of problem-based distance learning is seen as an appealing and effective tool for distance learning, promoting students' interactions and skills (Morgado, Mendes, & Proença, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rubrics assist students by providing clear criteria that can guide the development, review, and evaluation of their own work, a process particularly valuable when developing projects in a PBL environment (Guo, Saab, Post, & Wilfried, 2020). Sattarova, Groot, and Arsenijevic (2021) indicated that students' satisfaction is a fundamental requirement for the successful implementation of the PBL methodology in classrooms. This is because the substitution of traditional teaching methods is only possible if students support and are satisfied with alternative met hodologies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This is because the substitution of traditional teaching methods is only possible if students support and are satisfied with alternative met hodologies. Several studies demonstrate a high level of satisfaction among students with regard to PBL, as it positively impacts their interest, grades, effort, teamwork, and skills (Oliveira & Cardoso, 2021;Sattarova et al, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%